HIGH-INTENSITY LASER THERAPY TO TREAT NEUROPATHIC PAIN IN POST-HERPETIC NEURALGIA - Richard Suherlim; I Putu Eka Widyadharma; I Made Oka Adnyana; Anak Agung Ayu Suryapraba (MNJ (Malang Neurology Journal), 2023)
Post-herpetic neuralgia (PHN) is chronic neuropathic pain that is felt for at least 3 months or more at the site of the rash due to herpes zoster infection. Epidemiological studies get a prevalence of 0.49 cases of PHN per 1000 people per year. The clinical manifestation of PHN is chronic pain on the skin lesions due to herpes zoster infection. The therapy that is commonly used as the first line is the provision of pharmacotherapy such as gabapentin or pregabalin. An 83-year-old male patient with a diagnosis of PHN that had been felt for 5 years. He has been taking drugs for 5 years but the pain has not improved. The patient is given high-intensity laser therapy. After 5 treatments with an interval of 1-2 weeks, pain was significantly reduced from an 8/10 scale to 4/10. The frequency of occurrence of severe pain is also reduced from 5 times per day to only 1 time per day. The use of high-intensity laser therapy is not commonly used as a therapy for PHN. Based on its mechanism of action, the use of high-intensity laser therapy is worth considering because of its effectiveness in treating pain in a shorter time than low-intensity laser therapy.